Nutrition literacy and its related demographic factors among workers of Taraz Steel company, Chaharmahal and Bakhtiari, Iran - Yarmohammadi, Parastoo; Morowatisharifabad, Mohammad Ali; Rahaei, Zohreh; Khayyatzadeh, Sayyed Saeid; Madadizadeh, Farzan (Frontiers in Public Health, 2022)
Abstract Background: Nutrition is critical to prevent some chronic diseases. Nutrition literacy refers to ability to gain, understand and evaluate nutrition facts to choose appropriate foods. Nutrition literacy has recently drawn the attention of professionals with respect to health promotion. The purpose of this study was to investigate nutrition literacy and potentially related demographic factors among workers of a steel company in Chaharmahal and Bakhtiari province, southwest Iran. Methods: In this descriptive-analytical study in 141 workers of Taraz Chaharmahal Steel Factory in 2021, participants were selected by convenience sampling and a self-report nutrition literacy scale nativized to Iranians was used to collect data. Data were analyzed by SPSS 22 using Mann-Whitney U test, Kruskal-Wallis test and Spearman’s correlation coefficient. Results: About 75% of workers had adequate nutrition literacy and around 24% inadequate nutrition literacy. The highest percentage of mean score was obtained for determination of food groups (85.4%) and the lowest for calculation of food units (47%). The mean score of nutrition literacy was significantly higher in people with higher education (P=0.020). Also, people with adequate monthly salary attained a higher mean score on determination of food groups (P=0.021) and higher overall nutrition literacy (P=0.003) compared to other people. No relationship was observed between nutrition literacy and body mass index as well. Conclusion: Most workers have adequate nutrition literacy but their scores on calculation of food units are relatively low. It is essential for policymakers to collect information on the level of nutrition literacy in different populations, especially Iranian workers, to reduce the prevalence of nutrition-related chronic diseases.